Octahedron-dependent near-infrared luminescence in Cr3+-activated phosphors. (March 2022) - Zhao, F.Y.; Cai, H.; Zhang, S.Y.; Song, Z.; Liu, Q.L.
Abstract: Searching for broadband near-infrared (NIR) materials with high efficiency and excellent thermal luminescence stability is of great significance because of their widespread spectroscopic applications. Different element substitution can modulate the structure and crystal field of host lattice so as to regulate the luminescent properties. Herein, we report the octahedron-dependent NIR luminescence in Cr 3+ -doped KMP2 O7 (M = Ga, Sc, In, and Lu) phosphors and investigate the effect of octahedral environment on luminescent properties, aiming to provide guidance for host material selection. The decreased crystal field strength leads to the apparent spectral red shift from 815 to 900 nm for the samples of M = Ga to Lu. The small Stokes shift as well as weak electron–phonon coupling effect decreases the non-radiative transition probability and thus gives rise to the highest emission intensity and excellent thermal stability of Cr 3+ -doped KGaP2 O7 . The optimal sample, KGa0.89 P2 O7 :0.11Cr 3+, possesses an internal/external quantum efficiency of 55.8%/36.6%, and its integrated emission intensity at 423 K can maintain 68% of that at room temperature. Finally, we investigate the potential applications in non-destructive examination field by manufacturing a NIR phosphor-conversion light-emitting diode device. Highlights: Octahedron-dependent near-infrared (NIR) luminescence in Cr 3+ -doped KMP2 O7 (M = Ga, Sc, In, and Lu) is explored. Broadband NIR luminescence of KGaP2 O7 :Cr 3+ phosphor with high-efficiency and excellent thermal stability is reported. The application of KGaP2 O7 :Cr 3+ phosphor in non-destructive examination is demonstrated.